Self-rated health and physical disabilities due to heath problems - Souza, Mirian Carvalho de; Otero, Ubirani Barros; Almeida, Liz Maria de; Turci, Silvana Rubano Barretto; Figueiredo, Valeska Carvalho; Lozana, José de Azevedo (Revista de Saúde Pública, 2008)
OBJECTIVE: To evaluate self-rated health and physical disabilities due to health problems. METHODS: Population-based cross-sectional study carried out in 18 Brazilian cities between 2002 and 2005. There were interviewed 26,424 residents (aged 15 years or more) of households selected by a two-stage probabilistic sampling. Percentages and confidence intervals were calculated considering the study design effects. RESULTS: Poorer self-rated health status and physical disabilities were found among women, those aged 50 years old or more and those with lower education. In addition, higher percentages of fair or poor self-rated health were found in cities in Northern and Northeastern Brazil compared to those in Southern and Southeastern Brazil. CONCLUSIONS: Poorer health conditions in the North/Northeast compared to the South/Southeast regions reflect factors related to social inequalities, mainly lower education.